Microwave and ultrasound activation effect on cationization of corn and potato starches (2013)
AbstractThe aim of this study was to identify and compare the effect of ultrasound (US) and microwave (MW) irradiation on the assisted synthesis reaction to obtain cationic corn and potato starch derivatives, with cationizing agent (3-chloro-2-hydroxypropyl)-trimethylammonium chloride in solutionand in limited solvent conditions, known as a paste process. The starch derivatives were characterized by techniques, such as Fourier Transformed Infrared Spectroscopy, Thermo Gravimetric Analysis, Differential Scanning Calorimetry, Scanning Electron Microscopy and Atomic Force Microscopy.The application of both (MW) and (US) irradiation as energy sources permitted the shortening of the etherification time to minutes from the previously reported 18 hours of traditional heating. The results show the high potential of alternative energy sources to innovate and increase the efficiency of a technological starch derivatization process.Keywords: Cationic starch, characterization, microwave, synthesis, ultrasound.